Effect of heat treatment and storage period on the quality of traditionally fermented goat milk yoghurt - E. Suliman, Abdel Moneim; Alemam, Abbas H. O.; Ahmed Salih, Elzubier (Gezira Journal of Agricultural Science, 2023)
The objectives of the study were to investigate the effect of heat treatment and storage period on the chemical, microbiological analyses and sensory characteristics of yoghurt produced from goat milk. Milk was either raw or subjected to boiling or pasteurization and stored at 6 ºC for 1, 7 or 15 days. The results showed that the moisture, ash, protein, fat, and carbohydrate contents of raw goat's milk were 89 %, 0.75%, 3.36 %, 4.00 %, and 2.89%, respectively, while boiled milk contained 87.2 %, 0.70 %, 3.43 %, 3.96 % and 4.71% and pasteurized milk contained 88.33%, 0.68%, 3.50%, 4.2% and 3.29%, respectively. All types of yoghurts showed a gradual increase in protein and fat, while a gradual decrease was observed in moisture, ash and carbohydrates contents during storage. All types of yoghurts showed a gradual decrease in pH and lactose content while there were increases in the acidity and total soluble solid (TSS)  at the first day of storage. This decrease continued until the seventh day of storage, while the acidity gradually increased. The microbiological analyses revealed an increase in the microbial counts during storage and the highest increases were found in yoghurt samples prepared from raw milk. Moreover, coliforms were not detected in all samples. All types of yoghurt were highly accepted by the panelists who gave highest scores of flavour to the raw milk yoghurt.